2017
DOI: 10.12681/jhvms.14888
|View full text |Cite
|
Sign up to set email alerts
|

The status of Donkeys (Equus asinus) in Greece

Abstract: The paper presents, for the first time, information about donkeys (Equus asinus) in Greece. Most of the information was obtained from interviews of donkey owners, using a purpose built questionnaire. The population of donkeys in Greece showeda remarkable decrease over the last decades. From 508,000 in 1955, there were only 14,570 in 2008, a decrease of 97%. The existing donkeys were characterised by a large diversity in phenotypes. The lack of any breeding programme for donkeys, the importation of jacks from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, despite numerous benefits of donkey breeding, there was a large decline in the donkey population in Eastern Europe over recent years, as reported by Norris et al (2021). Although there are many breeds of donkeys (Laus et al, 2015), many Balkan countries have their distinctive donkey breeds, such as Istrian, North Adriatic and Littoral-Dinaric donkey in Croatia (Ivankovic et al, 2002), Arcadian donkey in Greece (Arsenos et al, 2017) and Balkan donkey, which is a large autochthonous breed found in Serbia (Kugler et al, 2008).…”
Section: Erdeljan Et Almentioning
confidence: 99%
“…However, despite numerous benefits of donkey breeding, there was a large decline in the donkey population in Eastern Europe over recent years, as reported by Norris et al (2021). Although there are many breeds of donkeys (Laus et al, 2015), many Balkan countries have their distinctive donkey breeds, such as Istrian, North Adriatic and Littoral-Dinaric donkey in Croatia (Ivankovic et al, 2002), Arcadian donkey in Greece (Arsenos et al, 2017) and Balkan donkey, which is a large autochthonous breed found in Serbia (Kugler et al, 2008).…”
Section: Erdeljan Et Almentioning
confidence: 99%
“…The main use of donkeys has traditionally been, and still largely is, for traction and transport of goods and people. For this reason, economic development with the mechanization of transport and agriculture has generally had dramatic impacts on donkey populations [11][12][13][14]. In Europe, the donkey population has declined by more than 80 percent since the Second World War.…”
Section: Introductionmentioning
confidence: 99%